2006
DOI: 10.4161/cbt.5.7.2812
|View full text |Cite
|
Sign up to set email alerts
|

Altered gene expression induced by ionizing radiation and glycolytic inhibitor 2-deoxy-glucose in a human glioma cell line: Implications for radio sensitization

Abstract: The glycolytic inhibitor 2-deoxy-D-glucose (2-DG) has been shown to enhance the cell death induced by radiation and other DNA damaging agents selectively in cells with high rates of glycolysis, like cancer cells. While energy linked modification of DNA and cellular repair processes have been suggested as possible mechanisms of sensitization, other effects such as global stress response cannot be excluded. In this pilot study, we have investigated the effect of 2-DG and radiation on the transcriptome in an atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Alterations in expression levels of many genes involved in damage response pathways including DNA repair and apoptosis, transcriptional regulators, cell signaling, besides energy metabolism have been reported that could significantly influence on the radiosensitization of tumor cells (Dwarakanath and Jain, 1987). A robust UPR was also induced by 2DG that contributes to the radiosensitization (Heminger et al, 2006). The 2DG-induced enhancement of radiation damage has been found to be directly proportional to the glucose usage, presence of hypoxia, and doses of 2DG and radiation (Dwarkanath et al, 2001;Khaitan et al, 2006), as our finding.…”
Section: Discussionsupporting
confidence: 82%
“…Alterations in expression levels of many genes involved in damage response pathways including DNA repair and apoptosis, transcriptional regulators, cell signaling, besides energy metabolism have been reported that could significantly influence on the radiosensitization of tumor cells (Dwarakanath and Jain, 1987). A robust UPR was also induced by 2DG that contributes to the radiosensitization (Heminger et al, 2006). The 2DG-induced enhancement of radiation damage has been found to be directly proportional to the glucose usage, presence of hypoxia, and doses of 2DG and radiation (Dwarkanath et al, 2001;Khaitan et al, 2006), as our finding.…”
Section: Discussionsupporting
confidence: 82%
“…Noxa is a well-studied BH3-only protein that has recently been described to play a role in glucose metabolism by promoting glucose uptake but directing glucose flux away from the glycolytic pathway by a yet uncharacterized mechanism (23). Noxa/ PMAIP1 mRNA had been observed to be induced in response to 2-DG (38), but its role in cell death had not been tested. In addition, Noxa has been shown to mediate death by ER stressors (22).…”
Section: Discussionmentioning
confidence: 99%
“…3-BrPA effectively kills colon cancer cells and lymphoma cells in a hypoxic environment in which the cancer cells exhibit high glycolytic activity and decreased sensitivity to common anticancer agents [143]. 2-deoxy-Dglucose inhibits glycolytic enzymes and has also produced encouraging antineoplastic results in vitro and in vivo [141, 143 -145] as well as sensitizing cancer cells to radiation [146,147] particularly in cancer cells with high rates of glycolysis [148].…”
Section: Expression Of Genes/proteins Involved In Energymentioning
confidence: 99%